PRE-SERVICE TEACHERS' PERCEPTIONS OF ENHANCING COUNSELING PROFICIENCY TO FACE MERDEKA CURRICULUM IN PRIMARY SCHOOL (SD/MI) - Nurdianah, Lutfiyan; Taufiq, Moh. (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
According to Law Number 14 of 2005 concerning Teachers and Lecturers, the role and duties of a teacher encompass being an educator, instructor, and mentor that be interpreted as a counselor. Therefore, students' perceptions of counseling services are crucial. By understanding students' perspectives, Lecturers can design more effective learning strategies aligned with the demands of the new curriculum, enhancing their guidance or counseling skills. This research aims to understand students' perceptions of how to improve counseling abilities. The study employs qualitative descriptive research and the subject are PGSD/PGMI students in Surabaya who are currently taking or have completed guidance and counseling courses. Based on data, prospective Pre-service Teacher's Counseling Abilities are perceived positively and diversely regarding ways to enhance counseling skills. Theoretically, students have demonstrated the ability to analyze their own needs for improving counseling skills. On average, students expect an increase in training intensity and opportunities to deepen practical experiences, supported by technology and facilities. With the heightened intensity of training and supportive facilities, students' counseling abilities and competencies are anticipated to gradually improve.